Development and reprotuction of Spodoptera eridania on natural hosts and artificial diet - Silva,A. (2019)
Abstract The development and reproductive potential of Spodoptera eridania (Stoll, 1782) (Lepidoptera, Noctuidae) was compared on natural and artificial diets. Its biology was determined under laboratory conditions, providing an artificial diet, leaves of white clover and the peach cultivar 'Chimarrita' and fruits and leaves of the apple cultivar 'Gala'. Larvae of S. eridania could not complete their biological cycle when fed on apple fruits or peach leaves. The artificial diet provided the shortest development time, with a cycle of 28.5±0.14 days from egg to adult and 37.3% total viability. Apple leaves led to a longer development time from egg to adult (62.8±1.22 days) and lower total viability (23%) and white clover provided the highest total viability (54.3%). The results showed that S. eridania can use white clover and apple leaves to develop normally in apple orchards. The reduction of food sources such as white clover used by the larvae results in infestation and damage to fruits from “test bites”.